Portugal : Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report, 2010)
This 2009 Article IV Consultation highlights that the global economic crisis has severely affected the Portuguese economy. Output will likely contract by almost 3 percent in 2009, driven by sharp falls in exports and investment. Despite a substantial rise in unemployment to nearly 10 percent, wage growth remained brisk. Encouragingly, some signs of adjustment are emerging, as prices have fallen faster than in the euro area. Executive Directors have encouraged the authorities to prepare a credible fiscal consolidation plan that would prevent further deterioration in fiscal balances.